The inhibitory effect of neurotropin on inflammation in rats with lumbar disc herniation based on the c-JNK/CXCL1 signaling pathway: The inhibitory effect of neurotropin on inflammation - Wu, Zhenyu; Gong, Shaohua; Zheng, Yuxin; Liang, He (Cellular and Molecular Biology, 2022)
This study aimed to investigate the inhibitory effect and mechanism of neurotropin on inflammation in rats with lumbar disc herniation. For this purpose, forty-eight rats were randomly divided into sham group, autologous nucleus pulposus transplantation model group (NP group), neurotropin treatment group (NP+NT group), and solvent [normal saline (NS)] control group (NP+NS group). After 7 days of intervention, the mechanical paw withdrawal threshold (PWT) and thermal paw withdrawal latency (PWL) of the rats were measured, and the expression levels of Iba-1, c-JNK and CXCL1 in spinal cord tissues were measured by Western blot. The levels of tissue-associated inflammatory and anti-inflammatory factors in the spinal cord were detected by ELISA. Results showed that Neurotropin significantly alleviated mechanical and thermal hyperalgesia induced by NP transplantation and reduced levels of Iba-1, c-JNK, and CXCL1 proteins in the spinal cord tissue. In addition, neurotoxins also lowered concentrations of the inflammatory factors IL-1β, IL-6 and TNF-α. It was concluded that Neurotropin has an inhibitory effect on lumbar disc herniation-induced spinal cord inflammation through inhibition of the c-JNK/CXCL signaling pathway.